Post‐rift magmatic evolution of the eastern North American "passive‐aggressive" margin. (9th January 2017) - Mazza, Sarah E.; Gazel, Esteban; Johnson, Elizabeth A.; Bizimis, Michael; McAleer, Ryan; Biryol, C. Berk
Abstract: Understanding the evolution of passive margins requires knowledge of temporal and chemical constraints on magmatism following the transition from supercontinent to rifting, to post‐rifting evolution. The Eastern North American Margin (ENAM) is an ideal study location as several magmatic pulses occurred in the 200 My following rifting. In particular, the Virginia‐West Virginia region of the ENAM has experienced two postrift magmatic pulses at ∼152 Ma and 47 Ma, and thus provides a unique opportunity to study the long‐term magmatic evolution of passive margins. Here we present a comprehensive set of geochemical data that includes new 40 Ar/ 39 Ar ages, major and trace‐element compositions, and analysis of radiogenic isotopes to further constrain their magmatic history. The Late Jurassic volcanics are bimodal, from basanites to phonolites, while the Eocene volcanics range from picrobasalt to rhyolite. Modeling suggests that the felsic volcanics from both the Late Jurassic and Eocene events are consistent with fractional crystallization. Sr‐Nd‐Pb systematics for the Late Jurassic event suggests HIMU and EMII components in the magma source that we interpret as upper mantle components rather than crustal interaction. Lithospheric delamination is the best hypothesis for magmatism in Virginia/West Virginia, due to tectonic instabilities that are remnant from the long‐term evolution of this margin, resulting in a "passive‐aggressive" margin that records multiple magmatic events long after rifting ended. Key Points: Bimodal late Jurassic volcanics in Virginia‐West Virginia produced by tectonic instabilities remnant of the rifting of Pangea The Eastern North American passive margin is characterized by pulses of postrift alkaline magmatic activity up to 150 Ma following rifting Pulses of magmatism and rejuvenation events in Eastern North American margin fail to fit the traditional passive‐margin definition